Analysis of Accounting Information Systems In Merchantability Inventory Control In Cv. Multicraft - Aulia Wahyu Widya Putri; Yanna Eka Pratiwi; Siwidyah Desi Lastianti (Journal of Economy, Accounting and Management Science (JEAMS), 2023)
The objectives to beachieved in this study are : to datermine the extent to which the accounting information system for controlling merchandise inventory is carried out effectively and efficiently on CV. MULTICRAFT. The steps to achieve the objectives of this research are : 1. Analysis the accounting information system for internal control of merchandise inventory on CV. MULTICRAFT, 2. Identify the problems and causes by CV. MULTICRAFT. From the results of the research and analysis carried out, it can be concluded that : 1. With the procedures that have been carried out, there are still some problems in CV. MULTICRAFT, the number of stock items is a lot different, and the inventory of merchandise is insufficient, 2. The occurrence of dual functions and the volume of work that high, which makes work inefficient, 3. There are 5 Standard Operating Procedure (SOP) that can be applied in the company so that the company’s internal control can be more optimal and better.